不同工艺市售芝麻油的气味活性成分 和感官品质差异分析Difference of aroma-active compounds and sensory quality of commercial sesame oil products produced by different processes - 翟卓青1,2，尹文婷1,2，汪学德1,2，马雪停1,2，杨忠欣3 ZHAI Zhuoqing1,2, YIN Wenting1,2, WANG Xuede1,2, MA Xueting1,2, YANG Zhongxin3 (Zhongguo youzhi, 2023)
旨在为芝麻油企业提高其产品的香气品质提供参考，以我国市场上不同工艺的13个品牌畅销芝麻油产品为实验材料，利用溶剂辅助蒸发（SAFE）法萃取挥发性物质，气相色谱-嗅闻-质谱（GC-O-MS）法和感官评价比较其气味活性成分和感官品质差异。结果表明：低温压榨芝麻油的气味活性成分以醛类、烯烃和醇类为主，生芝麻味最强；石磨水代和高温压榨芝麻油的气味活性成分以美拉德反应杂环类产物为主，具有较强的炒芝麻味、炒坚果味和焦香味；石磨水代芝麻油的苯酚类物质含量最高，烟熏味最强；高温压榨芝麻油的苦味最强。综上，不同工艺的市售芝麻油气味活性成分和感官品质具有显著差异。To provide reference for sesame oil enterprises to improve the aroma quality of their products, with 13 brands best-selling commercial sesame oils with different processes on the Chinese market were materials, volatile substances were extracted by solvent-assisted evaporation (SAFE) method, and the differences of aroma-active compounds and sensory quality were analyzed by gas chromatography-olfactometry-mass spectrometry (GC-O-MS) method and sensory descriptive analysis, respectively. The results showed that the aroma-active compounds in the cold-pressed sesame oils were dominated by aldehydes, alkenes and alcohols, and the cold-pressed sesame oils had the strongest raw sesame flavor. The aroma-active compounds in the aqueous-extracted and high temperature-pressed sesame oils were mainly the Maillard reaction products heterocyclic substances, giving the sesame oils strong roasted sesame flavor, nutty and burnt flavor. The aqueous-extracted sesame oils had the highest concentration of volatile phenolic compounds and the strongest smoky flavor. The bitter taste in the high temperature-pressed sesame oils was the strongest. In conclusion, the aroma-active compounds and sensory quality of sesame oil produced by different processes are significantly different.